Kewiralembagaan Kyai dalam Menginovasi Institusi Pesantren - Prastyanto, Ginanjar (IAI Darussalam, 2024)
This article seeks to explore the institutional innovation practices of Islamic boarding schools carried out by Kyai Malik, namely from being just an institution for cadre cadre of ulama to an institution that also cadres entrepreneurs. Since its inception, Islamic boarding schools have had an innovative character. This institution is the result of innovation from religious educational institutions in the Hindu-Buddhist era. As time goes by, the kyai also make institutional innovations in the Islamic boarding schools they care for, namely by adopting schools at various levels. However, on the other hand, it turns out that schools are less able to carry out their duties as educational institutions that prepare their students to become people who are able to live independently. Responding to this situation, Kyai Malik carried out institutional entrepreneurship practices by innovating his Islamic boarding school, in the form of developing learning methods based on real reality. Real reality-based learning methods are educational methods that adapt entrepreneurial practices directly into the learning process.